Comparative Physiochemical and Anatomical Changes of Metabolic Pathways in Women Because of Obesity, A Clinical Study - Rizwana Hussain, Sehar Khowaja, Jazib Andleeb, Arisha Sana Memon, Alina Saqib, Naveed Shuja (Pakistan Journal of Medical & Health Sciences, 2022)
Aims and objectives: To identify physiological, biochemical and anatomical changes in obese women of our community for health awareness were the aims and objectives of this study and it was conducted from October 2021 to March 2022 at different medical institutes of Pakistan comparatively. Materials and Methods: 300 total women of 30-40 years of age group were selected and divided them into two different groups. In Control group there was 100 normal women while in obese group, 200 women were sort out. BMI, skin fold thickness, random glucose levels, uric acid levels, systolic and diastolic blood pressure and Disc height index were measured comparative. Raw data of all variables were presented through bio-statistically model SPSS-2018. Mean standard deviation and significant (p<0.05) changes were consider for the description of obtained results. Results: Different parameters such as BMI, skin fold thickness, systolic and diastolic blood pressure, disc height index, random glucose and uric acid levels of group-2 (34.12 ± 0.01, 33.2±0.01, 140.01± 0.04, 90.01± 0.01, 6.6 ± 0.04, 150.11± 0.04, 7.02± 0.01) showed a significant changes (p<0.05) than group-1(20.07± 0.03, 28.6±0.04, 118.02± 0.01, 69.02± 0.02, 7.4 ± 0.02, 130.01± 0.02, 4.12± 0.03) randomly. Conclusion: In this study BMI, skin fold thickness, systolic and diastolic blood pressure, disc height index, random glucose and uric acid levels are biomarkers were showed a significant changes in obese women as compared with the normal women. It has seen that obesity caused severe metabolic changes in the biological system which is so harmful for human health.